2007
DOI: 10.1016/j.febslet.2006.12.046
|View full text |Cite
|
Sign up to set email alerts
|

Role of Neu4L sialidase and its substrate ganglioside GD3 in neuronal apoptosis induced by catechol metabolites

Abstract: Mammalian sialidases are key enzymes in the degradation of glycoconjugates. Neu4L sialidase is localized to mitochondria and specifically expressed in brain. To elucidate the pathophysiological roles of Neu4L in the nervous system, we investigated the possible involvement of Neu4L in the apoptotic neurodegeneration under the existence of catechol metabolites generated by tyrosinase. We demonstrated that: (i) the expression level of Neu4L was dramatically decreased prior to apoptosis; (ii) the apoptotic phenoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 51 publications
1
32
1
Order By: Relevance
“…These Neu4 isoforms are also differentially expressed in a tissue-specific manner. In the brain, muscle and kidney, they contain both the long and short forms, while in the liver and the colon they are predominantly the short form as revealed by RT-PCR [46]. Both isoforms of Neu4 possess broad substrate specificity, including activity towards mucin.…”
Section: Discussionmentioning
confidence: 97%
“…These Neu4 isoforms are also differentially expressed in a tissue-specific manner. In the brain, muscle and kidney, they contain both the long and short forms, while in the liver and the colon they are predominantly the short form as revealed by RT-PCR [46]. Both isoforms of Neu4 possess broad substrate specificity, including activity towards mucin.…”
Section: Discussionmentioning
confidence: 97%
“…We have recently reported that in SAECs, at the mRNA level, NEU2 and 4 are expressed at 7.7 and 13.8%, respectively, relative to NEU3 (31). Furthermore, compared with NEU3 (36,63), the catalytic activities of NEU1, 2, and 4 for gangliosides are less clear (19,56,65).…”
Section: Resultsmentioning
confidence: 99%
“…Several sialidases are expressed in the human brain and are suggested to be involved in the mitochondrial apoptotic pathway in neuronal cell death (Yamaguchi et al, 2005;Hasegawa et al, 2007). Inhibition of sialidases in the brain may be associated with the abnormal behavior following oseltamivir medication.…”
Section: Active Efflux Of Oseltamivir By P-gp At the Bbbmentioning
confidence: 99%